Penimbangan Posyandu, Pemberian Imunisasi, dan Suplementasi Vitamin A pada Balita Stunting - elya sugianti (Universitas Pekalongan, 2021)
Stunting has a serious impact on the quality of human resources. Increasing access to health services is the effort of the Government of Indonesia to reduce stunting cases. This study aims to analyze the relationship between access to health services such as weighing of integrated services post, immunization, and supplementation of vitamin A with stunting in children aged 24-59 months. A case-control study was conducted on 292 samples which were divided into 146 case groups and 146 control groups. Data were collected by interview respondents, and documentation, and measurement. Data analysis used univariate and bivariate analysis with chi-square test. The results showed that there was no relationship between weighing of integrated services post (p=0.42), immunization (p=0.58), and supplementation of vitamin A (p=0.06) with stunting in children aged 24-59 months. Access to adequate health services will not be effective to reduce stunting cases if it is not balanced with good nutrition and health practices from mothers of children under five. Nutritional counseling and assistance from health workers are needed intensively from pregnancy to the first two years of life, especially for mothers with low education and less exposure to mass media and electronics. Keywords: Stunting, weighing of integrated services post, immunization, supplementation of vitamin A